Cancer-risk by family history and mismatch-repair mutation in Lynch syndrome. (2nd June 2020) - Marques-de-Sá, Inês; Castro, Rui; Pita, Inês; Dinis-Ribeiro, Mário; Brandão, Catarina
Abstract: Introduction: Surveillance of Lynch syndrome (LS) is recommended to reduce cancer-risk. There is an increased awareness that cancer-risk may vary with mismatch-repair mutation and family history. However, gene-specific and family-specific surveillance are not recommended. Therefore, we aimed to estimate the cumulative incidence of lesions and to assess the cancer-risk by family history and mismatch-repair mutation (MMR). Methods: Single-centre retrospective cohort of all individuals ( n  = 241) in a specialized institution was conducted. Results: Forty-eight percent of individuals inherited MSH2 mutations, 32% MLH1, 15% MSH6 and 5% PMS2. The calculated cumulative incidence for any cancer increased with age. By age 70, the cumulative incidence for low-risk, high-risk adenomas and CRC was estimated at 66.6%, 57.7% and 25.7%, respectively. By age 70, the cumulative incidence of endometrial cancer (EC), gastric cancer and urinary tract cancer was estimated at 17.3%, 3.3% and 12.6%, respectively. MLH1 and MSH2 mutation carriers had lower mean age of CRC diagnosis than MSH6 and PMS2 [MLH1:44(CI95% 38–50); MSH2:43(CI95% 40–47); MSH6:52(CI95% 45–59); PMS2:46(CI95% 35–57)]. The risk of EC was higher when family history was present (RR = 2.39, CI95%[1.3;4.6]). MSH6 mutation carriers had higher risk of EC comparative to other MMR mutation carriers (RR = 1.9, p  = .09). The risk of urinary tract cancer was higher with MSH2 (RR = 8.4, CI95%[2.7;25.9]) and positive family history (RR = 10.8, CI95%[1.4;82.8]). Conclusion: This cohort demonstrates the effectiveness of LS surveillance and suggests possible tailored surveillance strategies by gene mutation and family history.